2020
DOI: 10.1101/2020.07.15.205427
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endothelial reprogramming by disturbed flow revealed by single-cell RNA and chromatin accessibility study

Abstract: SUMMARYDisturbed flow (d-flow) induces atherosclerosis by regulating gene expression in endothelial cells (ECs). For further mechanistic understanding, we carried out a single-cell RNA sequencing (scRNAseq) and scATACseq study using endothelial-enriched single-cells from the left- and right carotid artery exposed to d-flow (LCA) and stable-flow (s-flow in RCA) using the mouse partial carotid ligation (PCL) model. We found 8 EC clusters along with immune cells, fibroblasts, and smooth muscle cells. Analyses of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 72 publications
4
31
0
Order By: Relevance
“…KLK10 mRNA (Figure 1g), KLK10 protein in cell lysates (Figure 1h,i), and secreted protein in the conditioned media (Figure 1j) were decreased by OS and increased by LS, confirming the role of KLK10 as a flow-sensitive gene and protein in vivo and in vitro. We further confirmed the flow-dependent expression of Klk10 by re-analyzing the single-cell RNA sequencing (scRNAseq) and ATAC sequencing (scATACseq) data sets that we recently published using the PCL model 38 . For the scRNAseq and scATACseq study, single-cells and -nuclei obtained from the LCAs and RCAs, respectively, at 2 days or 2 weeks after the PCL were used.…”
Section: Klk10 Expression Is Increased By S-flow and Decreased By D-flow In Ecs In Vitro And In Vivosupporting
confidence: 62%
“…KLK10 mRNA (Figure 1g), KLK10 protein in cell lysates (Figure 1h,i), and secreted protein in the conditioned media (Figure 1j) were decreased by OS and increased by LS, confirming the role of KLK10 as a flow-sensitive gene and protein in vivo and in vitro. We further confirmed the flow-dependent expression of Klk10 by re-analyzing the single-cell RNA sequencing (scRNAseq) and ATAC sequencing (scATACseq) data sets that we recently published using the PCL model 38 . For the scRNAseq and scATACseq study, single-cells and -nuclei obtained from the LCAs and RCAs, respectively, at 2 days or 2 weeks after the PCL were used.…”
Section: Klk10 Expression Is Increased By S-flow and Decreased By D-flow In Ecs In Vitro And In Vivosupporting
confidence: 62%
“…We further confirmed the flow-dependent expression of KLK10 by re-analyzing the single-cell RNA sequencing (scRNAseq) and ATAC sequencing (scATACseq) data sets that we recently published using the PCL model 38 . For the scRNAseq and scATACseq study, single-cells and -nuclei obtained from the LCAs and RCAs, respectively, at 2 days or 2 weeks after the PCL were used.…”
Section: Introductionsupporting
confidence: 61%
“…Interestingly, we found that HTRA1 was upregulated by OS in HAECs (Figure 7e,g), indicating HTRA1 itself is shear sensitive. This finding was further validated by qPCR in HAECs (Figure S12a) and by scRNAseq (Figure S13) and scATACseq analyses (Figure S14) in the mouse PCL study 38 . These results show KLK10 and HTRA1 expression are inversely regulated by flow.…”
Section: Htra1 Binds Klk10 Regulating Its Anti-inflammatory and Barrier Protective Functionmentioning
confidence: 59%
See 1 more Smart Citation
“…A recent study that used scRNA‐seq and scATAC‐seq to assess the molecular response of BECs to carotid artery ligation revealed reprogramming of enhancer accessibility that was linked to changes in gene expression and cell function. [ 154 ] It will be interesting to determine if lineage‐dependent differences in local chromatin composition impact endothelial function during development and in disease. This functional specialization may include differential control of metabolism, vasorelaxation, angiocrine secretion, disease progression, and organ regeneration.…”
Section: Discussionmentioning
confidence: 99%